Family Interfere With Work Conflict: Dampaknya Pada Kepuasan Dalam Bekerja, Kinerja, Dan Niat Untuk Keluar Dari Pekerjaan - Prajogo, Wisnu (208-7721)
This  research  examined  the  influence  of  family interfere  with  work conflict  to job  satisfaction,performance and intention to leave, and also the influence of job satisfaction to performance and intention to leave. Survey conducted on 128 bank employees found several findings. First, family interfere  with  work  conflict  has  negative  influence  to  job  satisfaction.  Second,  job  satisfaction has positive influence to performance. Third, job satisfaction has negative influence to intention to leave. Fourth, family interfere with work conflict has negative influence to job performance. Fifth, family interfere with work conflict has positive influence to intention to leave.Keywords: family interfere with work conflict, job satisfaction, job performance, intention to leave